A Pragma-Dialectical Approach to Political Discourse Analysis: A Case Study of the Former United State Trade Representative Ron Kirk’s Remarks on the Poultry Case - Wen, Shi (Sinología hispánica. China Studies Review, 2016)
Under the research framework of Pragma- Dialectics, this paper analyses and evaluates the former United State trade representative Ron Kirk’s remarks on the trade conflict of poultry. Through this case study, I intend to develop a pragma-dialectical approach to the political discourse. Based on the argumentative reconstruction, strategic maneuvering analysis and critical evaluation of the remarks, this paper finds that even if Ron Kirk’s remarks look reasonable apparently, there are still some fallacies hidden in them. In order to make the US government benefit most from the trade conflict, after considering comprehensively of the potential topics, audience demands, and presentational devices, Ron Kirk maneuvers strategically by choosing beneficial starting points and arranging argumentative schemes technically. By doing so, he can transmit Anti- China ideology to the international society imperceptibly. In addition, by taking into consideration the background information of the poultry case and the Ten Commandments of a critical discussion, this paper reveals that, the accepted starting points and the argument schemes are abused in Ron Kirk’s remarks. Through the case study, this paper tries to study political discourse from Pragma-Dialectical approach and provide feasible analytical methods and reasonable evaluative standards for the political discourse analysis, so that a new perspective will be offered for researches on political discourse.